Post Treatment Acidizing Study on Carbonate Rock with Wormhole Radius Method - Ageng Warasta; Ratnayu Sitaresmi; Pri Agung Rakhmanto; Esaim Mustafa Abrahim Omar (Penerbitan Universitas Trisakti, 2021)
The problem that generally occurs in production activities is that wells in producing conditions has a low production rate. This could be due to the low permeability value of the reservoir or the increase of the skin factor of the reservoir due to formation damage. This matrix acidizing stimulation method is considered as an effective method in terms of activity costs and the success ratio in carbonate rocks. One of the successes of increasing the permeability around the well area depends on how far the wormholes are formed around the well. The results showed that the fractal dimension and wormhole radius model approach can be used to analyze the post treatment skin effect after validating the field data. Further analysis was carried out by involving limestone and dolomite reservoirs which have different characteristics in terms of porosity, permeability and fractal dimensions. The two reservoirs require different volumes of acid injection to produce the same reduction in skin factor. In this research, it is found that the parameters of permeability ratio, fractal dimensions, acid concentration, rock porosity and type of lithology affect the post treatment skin factor.